Pengaruh Inflasi Dan Suku Bunga Terhadap Return Saham Dengan Profitabilitas Sebagai Variabel Intervening Di Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2013-2015: The Effect of Inflation and Interest Rates on Stock Returns with Profitability as an Intervening Variable in Banks Listed on the Indonesia Stock Exchange 2013-2015 - Wiratno, Adi; Kurniasari, Wulan; Yusuf, Muhammad (Journal of Accounting Science, 2018)
This study aims to prove empirically that inflation and interest rates have a direct infuence on stock returns with ROA as intervening variables on Bankings listed in Indonesian Stock Exchange. The purposive sampling method used has certain criteria on samplings which published financial statements in 2013-2015 with documents in the average of a quartal of 10 banking industries based on Bank 3 book. This research shows the direct and indirect effect of using multiple linear regression to prove contribution of independent variable to dependent partially and simultaneously to stock return and using path analysis as the best intervening effect. Partial test result (t test) inflation and interest rate have direct influence to stock return with result of data of t-calculate> t-table is -4.000> 1.658 and -3.734> 1.658. ROA does not have a direct influence on stock return partial test results (Test t) t-count <t-table is 1.531 <1.658. Inflation has an indirect effect on stock return through ROA the result of 0.012 and the interest rate has indirect effect on stock return through ROA results 0.011. So, this research results can be used as information for investors and stakeholders in determining a good investment in Banking